Physical exercise improved muscle strength and pain on neck and shoulder in military pilots - Heng, Wei; Wei, Feilong; Liu, Zhisheng; Yan, Xiaodong; Zhu, Kailong; Yang, Fan; Du, Mingrui; Zhou, Chengpei; Qian, Jixian (Frontiers in Physiology, 2022)
Purpose To evaluate the effects of physical exercise on neck and shoulder muscle strength and pain in military pilots. Method Embase, PubMed, and Cochrane Library databases were searched studies published up to April 1, 2022. Studies that met the screening criteria were included in the final meta-analysis. We calculated neck and shoulder maximal voluntary isometric contractions (MVICs), prevalence of pain, and pain intensity. Heterogeneity was explored by subgroup and sensitivity analyses. Result A total of 15 studies with 907 participants were included. In the exercise group, muscle strength was significantly increased in four directions of neck motion: flexion (standardized mean difference (SMD) = 0.45; 95% CI, 0.08 to 0.82), extension (SMD = 0.63; 95% CI, 0.27 to 1), right lateral flexion (Rtflx) (SMD = 0.53; 95% CI, 0.12 to 0.94), and left lateral flexion (Ltflx) (SMD = 0.50; 95% CI, 0.09 to 0.91). Subgroup analysis showed that fighter pilots, strength plus endurance training, and a follow-up period < 20 weeks exhibited more significant muscle strength improvements than helicopter pilots, simple strength training, and a follow-up period ≥ 20 weeks. Overall, the pooled odds ratio (OR) for the effect of physical exercise on the prevalence of neck pain was not statistically significant (I2 = 60%). Sensitivity analysis revealed that the heterogeneity was restored after removing each of two studies (I2 = 47%), and the pooled OR was statistically significant (OR = 0.46; 95% CI, 0.23 to 0.94, or OR = 0.47; 95% CI, 0.24 to 0.91). Furthermore, compared with observational studies (OS), the reduction in the prevalence of neck pain was more significant in randomized controlled trials (RCTs) (OR = 0.37; 95% CI, 0.18 to 0.78). No significant differences in the effects of exercise on shoulder muscle strength and neck and shoulder pain intensity were observed. Conclusion Physical exercise can improve neck muscle strength in military pilots. After removing studies that may be the source of heterogeneity, exercise showed a protective effect on neck pain, especially in RCTs. The conclusion that exercise had no effects on shoulder muscle strength and pain intensity should be taken with caution.